2003
DOI: 10.1046/j.1365-313x.2003.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Barley sex6 mutants lack starch synthase IIa activity and contain a starch with novel properties

Abstract: Analysis of barley shrunken grain mutants has identified lines with a novel high amylose starch phenotype. The causal mutation is located at the sex6 locus on chromosome 7H, suggesting the starch synthase IIa (ssIIa) gene as a candidate gene altered by the mutation. Consistent with this hypothesis, no evidence of SSIIa protein expression in either the starch granule or soluble fractions of the endosperm was found. Sequences of the starch synthase IIa gene, ssIIa, from three independent sex6 lines showed the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
212
3
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(250 citation statements)
references
References 49 publications
32
212
3
3
Order By: Relevance
“…This study also showed unambiguously that the large increase in apparent amylose content in the mutant starch was partly due to an increased amount of long chains of amylopectin. Similar effects on amylopectin structure by loss of starch synthase II activity were reported for mutants of pea (rug5) 18) and barley (sex6), 19) and Umemoto et al . 20) suggested reduced starch synthase II activity in japonica rice results in structural differences between japonica and indica rice amylopectins, which is similar to those of the wheat starches examined in this study.…”
Section: Molar Composition Of Amylose and Amylopectinsupporting
confidence: 80%
“…This study also showed unambiguously that the large increase in apparent amylose content in the mutant starch was partly due to an increased amount of long chains of amylopectin. Similar effects on amylopectin structure by loss of starch synthase II activity were reported for mutants of pea (rug5) 18) and barley (sex6), 19) and Umemoto et al . 20) suggested reduced starch synthase II activity in japonica rice results in structural differences between japonica and indica rice amylopectins, which is similar to those of the wheat starches examined in this study.…”
Section: Molar Composition Of Amylose and Amylopectinsupporting
confidence: 80%
“…2). Other starch mutants, such as the shrunken mutants of maize (Tracy, 2000), the wrinkled mutant of pea (Bhattacharyya et al, 1990) and the barley sex6 mutant (Morell et al, 2003) also exhibit a shrunken seed shape. As expected, the SW double mutant was amylose-free and cut kernels stained redbrown with iodine (data not shown).…”
Section: Textmentioning
confidence: 99%
“…The synthesis pathway of the rather complex amylopectin molecule includes soluble starch synthase (SS), starchbranching enzyme (SBE), and starch-debranching enzyme (DBE). Each individual SS isoform is believed to have a unique function in amylopectin synthesis Li et al, 2003;Morell et al, 2003;Morell and Myers, 2005). Distinct SBE isoforms are recruited for starch synthesis during particular stages of seed filling in barley (Mutisya et al, 2003).…”
mentioning
confidence: 99%